Designações de sujeitos na obra vocabulario gaúcho de Roque Callage - Echevarria, Felipe Rodrigues (2016)
The present work is inscribed in the History of Linguistic Ideas (HLI) that studies, mainly, the production of linguistic instruments, this has been done in Brazil since the 16th Century. Language tools are, according to Auroux (1992), the main pillars of our metalinguistic knowledge, resulting from the Technological Revolution of Gramatization. In addition to grammar and dictionaries, vocabularies and glossaries are also considered language tools. Our object of research is the work Vocabulario Gaúcho, produced in the year 1928 by the Santa Marian author Roque Callage, who collected typical entries spoken by the gaucho society. We understand that, among other factors, it is through the language that the gaucho builds his regional identity. Our corpus is structured as follows: from this vocabulary, we cut out 132 entries, using selection criteria that designate subjects. Soon after, we separate them into the following categories: 1. Those who designate social class; 2. Those who designate a geographical and belonging issue, which indicates where the subject comes from; 3. Those who designate the race/ethnicity of the subject; 4. Those that indicate the occupation and/or profession of the subject; 5. Those that have the physical characteristics of the subjects; 6. Those who designate women. After showing the meanings presented by these entries, we selected nine: bahiano, bruáca, china, chirú, chirúa, estancieiro, gasguita, gaúcho and morocha, mobilizing the concepts of designation, description and definition for analysis. The choice of these nine entries is due to the fact that they reveal the socio-historical conditions of the time in which Vocabulario Gaúcho was produced. Most of the entries in Callage's work are in the masculine, and the few that are in the feminine present pejorative senses, as in the case of bruáca, china, chirúa and gasguita. This analysis reveals a Rio Grande do Sul dominated by men, where the gaucho is highly valued; his qualities as virility and ability with the horse are exalted, while women, especially women from the countryside, as Hillaire (1997) tells us, remain restricted to the domestic sphere. Thus, we confirm the theoretical assumptions brought by Nunes (2006b), that dictionaries are discursive objects. Although our research object is a vocabulary, it presents functions similar to those of dictionaries, so that the designations presented by the analyzed articles are lined with history, especially in the history of Rio Grande do Sul. This brings a discourse about the history of the state.